Ethnobotany of Mendong Plants (Fimbristylis globusa) As Handicrafts in Wajak District of Malang Regency - Febriyana, Siti Fitrianti Aminah; Nadhifah, Ainun; Minarno, Eko Budi (Proceedings of the International Conference on Green Technology, 2019)
Mendong (Fimbristylis globusa) is a grass plant that morphologically looks similar to rice and is used for a variety of handicrafts. Handicrafts from mendong plants are often found in Blayu Village, Wajak District. The purpose of this research is to get information related to the utilization of mendong plant (Fimbristylis globusa). The type of research used is descriptive exploratory through survey and interview method. The community in Wajak District, specifically Blayu Village, Meduran and Bebekan Sub-village utilize mendong plants (Fimbristylis globusa) as handicrafts such as mats and ropes.